2013
DOI: 10.1111/bjh.12223
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics of extramedullary manifestations in multiple myeloma

Abstract: SummaryExtramedullary disease in patients with multiple myeloma is a rare event, occurring mostly in advanced disease or relapse. Outcome is poor and prognostic factors predicting the development of extramedullary disease have not been defined. We investigated cytogenetic alterations of myeloma cells in different extramedullary manifestations by adapting the fluorescence in situ hybridization (FISH) technique in combination with cytoplasmic immunoglobulin staining to study the cytogenetics of plasma cell tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 33 publications
9
64
3
Order By: Relevance
“…In contrast, Billecke et al reported that patients with MM and extramedullary involvement presenting different FISH findings in the EMPs compared to their bone marrow plasma cells. In their study, del(17p13) seems a strong marker for extramedullary progression [21]. Bone marrow genetic abnormalities are not associated with extramedullary spread per se, which also suggests that microenvironmental interactions appear to be important.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, Billecke et al reported that patients with MM and extramedullary involvement presenting different FISH findings in the EMPs compared to their bone marrow plasma cells. In their study, del(17p13) seems a strong marker for extramedullary progression [21]. Bone marrow genetic abnormalities are not associated with extramedullary spread per se, which also suggests that microenvironmental interactions appear to be important.…”
Section: Discussionmentioning
confidence: 89%
“…6 High LDH levels, anemia, thrombocytopenia, nonsecretory MM, and highrisk cytogenetic features are more frequent in patients with de novo EMM than in patients with classic MM. 16,21,22 Interestingly, the combination of high LDH level and high-risk cytogenetic features, parameters found to be more frequent in EMM, has been described to be associated with an ultrahigh risk of early progression or disease-related death in MM patients. 23 Moreover, the frequency of high-risk gene expression profiles (MAF and PR) is found to be higher in EMM patients.…”
Section: Biological and Clinical Features Of Emmmentioning
confidence: 99%
“…Among others, the two distinct cytogenetic aberrations del(17p13) and del(13q14) seem to occur more commonly in EMD when compared with MM with sole manifestation in bone marrow and have been suggested as markers for progression to EMD 7–10. EMD seems an advanced, cytologically distinct and more aggressive form of MM 7. Our case emphasises to actively consider MM and EMD in patients with known monoclonal gammopathy of unknown significance (MGUS) encountering a new medical problem, irrespective of the clinical presentation.…”
Section: Introductionmentioning
confidence: 89%